Auto-tuning PID Controller for Robotic Manipulators - Choi, Y.; Oh, Y.; Oh, S.R.; Chung, W.K. (Proceedings of the American Control Conference, 2003)
This paper suggests an auto-tuning method of PID trajectory tracking controller for robotic manipulators. In general, the PID trajectory tracking controller for mechanical systems shows the performance limitation. Since the control system including performance limitation can not have equilibrium points, we define newly the quasi-equilibrium region as an alternative for equilibrium point. Also, the quasi-equilibrium region is used as the target performance of the auto-tuning PID trajectory tracking controller. The auto-tuning law is derived from the direct adaptive control scheme, based on the extended disturbance input-to-state stability. Finally, experimental results show that the control performance is enhanced by an auto-tuning method assisting the achievement of target performance.